miR-122 inhibition in a human liver organoid model leads to liver inflammation, necrosis, steatofibrosis and dysregulated insulin signaling. - Hossein Sendi; Ivy Mead; Meimei Wan; Marjan Mehrab-Mohseni; Kenneth Koch; Anthony Atala; Herbert L Bonkovsky; Colin E Bishop (PLoS ONE)
To investigate the role of miR-122 in the development and regression of non-alcoholic fatty liver disease (NAFLD) in vitro, we used multicellular 3D human liver organoids developed in our laboratory. These organoids consist of primary human hepatocytes, Kupffer cells, quiescent stellate cells and liver sinusoidal endothelial cells. They remain viable and functional for 4 weeks expressing typical markers of liver function such as synthesis of albumin, urea, and alpha-1 p450 drug metabolism. Before mixing, hepatic cells were transduced with lentivirus to inhibit miR122 expression (ABM, CA). Immediately after the organoids were fully formed (day 4) or after 1 or 2 weeks of additional incubation (days 11 or 18), the organoids were analyzed using fluorescent live/dead staining and ATP production; total RNA was extracted for qPCR gene expression profiling. Our results show that miR-122 inhibition in liver organoids leads to inflammation, necrosis, steatosis and fibrosis. This was associated with increase in inflammatory cytokines (IL6, TNF), chemokines (CCL2, CCL3) and increase in a subset of Matrix Metaloproteinases (MMP8, MMP9). An altered expression of key genes in lipid metabolism (i.e LPL, LDLR) and insulin signaling (i.e GLUT4, IRS1) was also identified. Conclusion Our results highlight the role of miR-122 inhibition in liver inflammation, steatofibrosis and dysregulation of insulin signaling. Patients with NAFLD are known to have altered levels of miR-122, therefore we suggest that miR-122 mimics could play a useful role in reversing liver steatofibrosis and insulin resistance seen in patients with NAFLD.